(untitled) (Південний архів (історичні науки), 2022)
The purpose of this investigation is to determine the extent and nature of the influence of socio-political structures on the formation of volunteer battalions that participated in hostilities in eastern Ukraine in 2014–2015. Methods. The research methodology involves the application of the principles of historicism, the integrity of the study of historical sources and objectivity, the use of methods of analysis and synthesis, classification and systematization. The article reviews and analyzes previous research on this topic, as well as lists the public organizations and political parties that have influenced the formation of Ukrainian volunteer battalions. Results. According to the results of the study, the classification of volunteer units that participated in the Anti-Terrorist Operation in Eastern Ukraine, according to the criterion of influence on their formation of public organizations and political parties, based on analysis of previous research, media materials, published memoirs of participants, funded internal documentation formations and other available sources. Conclusions. The nature of the influence of specific socio-political structures on specific voluntary formations is studied. Eighteen public organizations and political parties that influenced the formation of Ukrainian volunteer battalions were identified. At the same time, the influence of only seven of these structures was decisive and only in the activities of seven volunteer formations (three units subordinated to the Internal Affairs agencies, a volunteer company subordinated to the State Border Service and three other voluntary formations that were not subordinated to any state structures). Regarding the influence of the international socio-political movement “Free Caucasus” on the formation of two more volunteer units, we can assume a similar influence, but due to lack of data we can not confirm or refute this assumption. As for other socio-political structures, their influence concerned only the formation of ideological sentiments of personnel and the creation of symbols of voluntary formations, and obviously only at the stage of their acquisition.